2022
DOI: 10.3390/genes13091612
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Uncoupling Protein Genes UCP1, UCP2 and UCP3 and Irisin Levels in Residents of the Coldest Region of Siberia

Abstract: Currently, it is known that irisin can participate in the processes of thermoregulation and browning of adipose tissue, and, therefore, it is possible that it is involved in the microevolutionary mechanisms of adaptation to a cold. The aim of this study is to investigate the relationship between the uncoupling protein genes (UCP1, UCP2, UCP3) and the irisin levels in the residents of the coldest region of Siberia. The sample consisted of 279 Yakut people (185 females, 94 males, average age 19.8 ± 2.03 years). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…A large study of Siberian populations identified candidate genes for adaptation to the cold, associated with energy and metabolic regulation, as well as contraction of vascular smooth muscle [9]. Besides, leptin and irisin, which play an important role in the processes of adaptation to the cold, become the focus of several other studies of the Yakutian cohort [13][14][15]. However, genetic studies for Siberian populations are often limited to mitochondrial DNA, Y chromosome or single-nucleotide polymorphisms [8,9,16,17], while epigenome-wide studies have not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…A large study of Siberian populations identified candidate genes for adaptation to the cold, associated with energy and metabolic regulation, as well as contraction of vascular smooth muscle [9]. Besides, leptin and irisin, which play an important role in the processes of adaptation to the cold, become the focus of several other studies of the Yakutian cohort [13][14][15]. However, genetic studies for Siberian populations are often limited to mitochondrial DNA, Y chromosome or single-nucleotide polymorphisms [8,9,16,17], while epigenome-wide studies have not been performed.…”
Section: Introductionmentioning
confidence: 99%